Back Cover: Development and validation of HPLC methodology for quantitative estimation of Efinaconazole in topical pharmaceutical formulation prepared in‐house for the treatment of onychomycosis. Issue 9 (15th September 2020) - Patani, Nikesh; Patel, Mrunali; Patel, Rashmin
Abstract : DOI: 10.1002/sscp.202000019 The cover picture shows the development, optimization and validation of an HPLC method for the assay of Efinaconazole in a topical formulation developed for the treatment of onychomycosis. The proposed HPLC method provides a simple and rapid tool for the routine quantitative estimation of Efinaconazole in quality control laboratories to ensure its safe and effective use.